A study of effect of alcohol on liver function tests (LFT) in Garhwal hills, India - Gogoi, Javin Bishnu; Bhasin, Mayank; Behera, Joshil Kumar; Gairola, Kailash; Baruah, Haren (International Journal of Research in Medical Sciences, 2017)
Background: There has been frequent researches on liver pathologies and its variables in the world. There is no known research carried on liver in Garhwal region. Uttarakhand is one area where the hill people are more habitual of alcohol abuse and alcoholism is more endemic here. Primary objective was to correlate alcohol intake and its effect on liver function test. Secondary objectives were to screen the patients for abnormal LFTs and to observe and understand changes needed in lifestyle to reduce risk of developing liver disorders. Methods: A cross sectional observational study was conducted on patients in a medical college in north India. The participants above the age of 10 years were included for the study. Results: Out of all the 150 study participants screened, 120 (80%) were detected to have abnormal liver function tests (LFT) (65 females and 55 males). Maximum numbers of participants with abnormal LFT belong to age group of 21-30 yrs. More frequent and higher amount of alcohol consumption was found to adversely affect the liver physiology. Conclusions: The most important risk factor for liver damage is frequent consumption of alcohol in excess of 4 pegs a day for males and 2 for females (One standard drink contains 10 grams of alcohol).